INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN STUDY IN MADRASAH: A CRITICAL REVIEW - Ratu Amalia Hayani; Maemunah; Nanah Sujanah; Mohammad Ahmad Bani Amer (CV. ADIBA AISHA AMIRA, 2023)
Information and Communications Technology (ICT) in madrasah education, with emphasis on a careful balance between the potential and challenges emerging from the use of technology. The potential advances of ICT in developing educational practices in the madrasah have gained widespread recognition, promising increased accessibility to a variety of resources as well as pedagogical differentiation capable of adapting to the individual learning needs of students. The method of research carried out in this research is literature by searching for literature that fits the context of the research. The results of the research show that ICT has offered to educational institutions that are not only public schools but also madrasas, but such developments not only integrate Islamic values of literacy but require dealing with infrastructure deficits, improving the capacity of educators, as well as formulating comprehensive policies that support the use of safe and effective technology in educational environments.